Environmental Subjects and Displays of Political Order: the Case of Ecology Monks in Northern Thailand - Amalia Rossi (Antropologia, 2014)
In the late eighties the Thai eco-Buddhist movement, led by a fragmented network of  Buddhist monks, mobilized in defense of the forested ecosystems and advocated rural  communities in forest and land conflicts against the state-corporation alliance. The  present discussion challenges the assumptions of those observers who described the local articulations of the eco-Buddhist movement in the nineties. By analyzing the life trajectory of two ecology monks operating in Nan and focusing on their representations of the righteous rural order, I will argue that the eco-Buddhist environmentalist approach,  throughout the decade 2000-2010, became a hegemonic force, supporting the  conservative powers’ effort to softly contrast the expansion of reformist social movements in the Northern Thai territories.